2006
DOI: 10.1016/j.braindev.2005.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Brain responses to tonal changes in the first two years of life

Abstract: Maturation of auditory perceptual and discrimination process within the first two years of life is investigated in healthy infants by examining event-related potentials (ERPs). High-density EEG signals were recorded from the scalp monthly between 3 and 24 months of age. Two types of stimuli (100 vs. 100 Hz for standard stimuli; 100 vs. 300 Hz for deviant stimuli; occurrence rate: 85:15%) were presented using an oddball paradigm. Latencies and amplitudes were compared across development. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 34 publications
4
33
0
Order By: Relevance
“…Second, we showed that a clear N250 is mostly absent in FT3 and PT6 infants but becomes stronger in FT6 and PT9 infants. These observations are also consistent with previous studies showing that full-term infants demonstrate a substantial increase in N250 from 3 to 6 months of age (13). Taken together, these results confirm that the neural substrate for auditory processing is less mature in the younger groups of both full-term and preterm infants.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Second, we showed that a clear N250 is mostly absent in FT3 and PT6 infants but becomes stronger in FT6 and PT9 infants. These observations are also consistent with previous studies showing that full-term infants demonstrate a substantial increase in N250 from 3 to 6 months of age (13). Taken together, these results confirm that the neural substrate for auditory processing is less mature in the younger groups of both full-term and preterm infants.…”
Section: Discussionsupporting
confidence: 82%
“…To estimate gains in neural maturation, we carried out periodical clinical assessments and also evaluated the early components of the event-related potentials (ERPs) that are associated with age-related changes in auditory processing. The latency and amplitude of the early speech ERPs change dramatically from 3 to 6 months of life in full-term infants (13,14). These changes are mainly correlated with changes in myelinization, synaptic efficacy, neural connectivity, and the anatomy of the infant's head (15,16).…”
mentioning
confidence: 99%
“…However, such mismatch negativities in newborns and infants usually persist for a longer interval and in a relatively late time window than those typically seen in adult data. Other studies instead reported that mismatch responses in infants are often a positivity between 200 msec and 450 msec, rather than an adult-like negativity (Dehaene-Lambertz & Baillet, 1998;Dehaene-Lambertz & Dehaene, 1994;Friederici, Friedrich, & Weber, 2002;Jing & Benasich, 2006;Leppänen, Eklund, & Lyytinen, 1997;Morr, Shafer, Kreuzer, & Kurtzberg, 2002;Novitski, Huotilainen, Tervaniemi, Näätänen, & Fellman, 2007). For example, Leppänen et al (1997) observed a positive mismatch response (P-MMR) peaking between 250 msec and 350 msec to the pure tone change in newborns.…”
mentioning
confidence: 85%
“…Rather the infants exhibited large frontocentral positivity to the deviant tone, and the toddlers showed no difference in event-related potential (ERP) responses between the standard and deviant. A number of other investigations have observed the positive mismatch response (p-MMR) in infants (Dehaene-Lambertz & Dehaene 1994;Leppänen et al 1997;Dehaene-Lambertz & Baillet 1998;Friederici et al 2002;Rivera-Gaxiola et al 2005;Jing & Benasich 2006, He et al 2007Tew et al 2009). In the study by Morr et al (2002), a larger tone difference of 1000 versus 2000 Hz was necessary for a clear MMN-like negativity to be observed in these younger age groups.…”
Section: Introductionmentioning
confidence: 93%